Preparation method of zirconium oxide-based composite material with shell-like amorphous-crystal dual-phase structure

By introducing the double-portal structure of imitation shell-crystal-crystal in the oxide material, the combination of graphene and silicon oxide is used to solve the problem of increasing the strength and toughness of oxide materials at the same time, realizing high-strength and high toughness oxidation oxidation Preparation of cymbal composite film.

CN119330704APending Publication Date: 2025-01-21BEIHANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411495885.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing zirconia materials have problems of poor brittleness and toughness, and it is difficult to improve their strength and toughness at the same time in practical applications.

Method used

Green and environmentally friendly graphene oxide is used as a template to prepare graphene oxide@zirconia nanosheet structural units through liquid phase synthesis, and is combined with silicon oxide and assembled into a composite material with a layered structure through a vacuum-assisted filtration strategy. Finally, a zirconia-based composite film with a shell-like amorphous-crystal dual-phase structure was obtained through high-temperature sintering.

Benefits of technology

It achieves high strength and high toughness of zirconia-based composite materials, breaking through the bottleneck of difficulty in improving the strength and toughness of ceramic materials at the same time. At the same time, the preparation process is simple, the conditions are mild, and it is universal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330704A_ABST
    Figure CN119330704A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of materials, and relates to a preparation method of a composite material with a microstructure similar to that of a biological material, in particular to a preparation method of a zirconium oxide-based composite material with a shell-imitating amorphous-crystal double-phase structure. Graphene oxide-zirconium oxide-silicon oxide nanosheets are obtained through a liquid phase synthesis method, then the nanosheets are assembled into a composite film through a vacuum-assisted suction filtration method, and finally the zirconium oxide-based composite material with the amorphous-crystal double-phase structure is prepared through high-temperature sintering. The specific method comprises the following steps: (1) mixing graphene oxide, zirconium salt and a silicon source to prepare a graphene oxide-zirconium oxide-silicon oxide nanosheet dispersion liquid; (2) uniformly mixing the solution in the step (1) with an organic matter, and carrying out vacuum filtration to obtain a composite film; and (3) carrying out high-temperature sintering on the film obtained in the step (2) to finally realize the preparation of the high-strength and high-toughness ceramic composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials and relates to a method for preparing a composite material with a microstructure similar to that of a biological material, and specifically relates to a method for preparing a zirconium oxide-based composite material with a shell-like amorphous-crystalline dual-phase structure. Background Art

[0002] Zirconia is resistant to high temperatures, has high strength, and good biocompatibility. It is widely used in many fields such as refractory materials, wear-resistant materials, and biomaterials, and has attracted the attention of more and more scientific researchers. However, zirconia also has the inherent disadvantages of ceramic materials such as brittleness and poor toughness, which makes it have certain limitations in practical applications. How to improve the strength and toughness of zirconia materials at the same time is the current difficulty. In recent years, improving mechanical properties by designing material structures has become a hot topic in the field of materials research.

[0003] In order to adapt to the environment, biological materials that have evolved for hundreds of millions of years have almost perfect structures and functions. The impact-resistant layer on the surface of the mantis shrimp's "elbow" is composed of highly arranged nanocrystals and amorphous organic matter. When impacted, the crystalline nanoparticles break and dislocate to form an amorphous region, which effectively absorbs and dissipates the impact energy; the amorphous organic network disperses and relieves the impact load through deformation, enhancing the toughness of the material. In addition, such an amorphous-crystal dual-phase structure also exists in the enamel, the hardest tissue in the animal body. Enamel is composed of crystalline hydroxyapatite nanowires and an amorphous organic matrix. The hydroxyapatite nanowires provide mechanical strength, while the organic matrix provides stability and corrosion resistance. The above studies show that the amorphous-crystal structure is conducive to improving the mechanical properties of the material, and nanocrystals usually provide mechanical strength, the interpenetrating amorphous network provides toughness, and the ultra-high mechanical strength also comes from the regular periodic arrangement of amorphous-crystals. This provides a new idea for the preparation of high-strength and high-toughness zirconia-based composite materials.

[0004] At present, most of the research on amorphous-crystal dual-phase structure exists in the field of metals. Although researchers have developed ceramic-based composite materials with dual-phase structures by imitating the preparation methods of metal materials, the preparation process is complex and the conditions are harsh, and both the crystal and the amorphous are in a disordered state, which limits the further improvement of mechanical properties. Therefore, it is urgent to develop a preparation method for zirconium oxide-based composite materials with an ordered amorphous-crystal dual-phase structure. Summary of the invention

[0005] The purpose of the present invention is to address the limitations of existing preparation methods, use green and environmentally friendly graphene oxide as a template, and widely used zirconium oxide, silicon oxide, etc. as raw materials, and innovatively propose a method with mild experimental conditions, simple synthesis, and universal assembly strategy to prepare a zirconium oxide-based composite material with a shell-like amorphous-crystalline dual-phase structure. The present invention obtains graphene oxide @ zirconium oxide nanosheet structural units and graphene oxide @ zirconium oxide @ silicon oxide nanosheet structural units in succession through a simple liquid phase synthesis method, and then assembles them into a composite material with a layered structure with the help of a vacuum-assisted filtration strategy, and then sinters at high temperature to remove graphene oxide and organic binders on the one hand, and sinter the ceramics on the other hand, and finally obtains a zirconium oxide-based composite film with a shell-like amorphous-crystalline dual-phase structure. It includes the following steps:

[0006] The first step is to add 4-10 mL of concentrated hydrochloric acid and 10-20 g of tris(hydroxymethyl)aminomethane to 1 L of ultrapure water to prepare a buffer solution with a pH value of 5-8. Graphene oxide and zirconium oxychloride octahydrate are sequentially added to the buffer solution, and stirred at 40-90° C. for 1-7 hours; wherein the concentration range of the graphene oxide in the mixed solution is 0.05-0.17 mg / mL; the concentration range of the zirconium oxychloride octahydrate in the mixed solution is 0.08-1.00 mg / mL;

[0007] The second step is to centrifuge the solution obtained in the first step at 4000-9000 r / min for 5 minutes, wash the obtained precipitate with ultrapure water for 1-5 times, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide nanosheet dispersion by ultrasonic treatment for 10-30 minutes, and then fix the volume for subsequent use;

[0008] The third step is to add the graphene oxide @ zirconium oxide nanosheet dispersion into 2L of anhydrous ethanol to obtain a uniformly dispersed brown-yellow suspension. Then, tetraethyl silicate and ammonia water are added thereto in turn, and the reaction is stirred at 20-50°C for 2-9 hours; wherein the concentration range of the graphene oxide @ zirconium oxide nanosheet in the mixed solution is 0.01-0.1 mg / mL; the volume fraction of the tetraethyl silicate in the mixed solution is 0.01%-0.1%; the volume fraction of the ammonia water in the mixed solution is 7%-14%;

[0009] The fourth step is to centrifuge the reaction solution obtained in the third step at 4000-9000 r / min for 5 minutes, wash the obtained precipitate with anhydrous ethanol and deionized water for 1-5 times respectively, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide @ silicon oxide nanosheet dispersion after 10-30 minutes of ultrasonic treatment, which is recorded as solution 1, and fix the volume for subsequent use;

[0010] Step 5: weigh 20-800 mg of organic matter using an analytical balance, add deionized water and stir to obtain a uniform solution, which is recorded as solution 2;

[0011] Step 6: Measure 5-10 mL of solution 2 into a 50 mL beaker, add 10-50 mg of graphene oxide @ zirconium oxide @ silicon oxide nanosheet solution 1, and then dilute to 40 mL with deionized water. Stir at room temperature for 6-40 hours, and then assemble the nanosheets into a composite film by vacuum assisted filtration to finally obtain a black film sample.

[0012] Step 7: Place the film sample obtained in step 6 in a tube furnace and calcine at 500-1200° C. for 0.5-3 h to finally obtain a white composite film sample. In the present invention, unless otherwise specified, the chemicals used can be used directly without further purification.

[0013] In the present invention, unless otherwise specified, the devices, instruments, equipment, materials, processes, methods, steps, preparation conditions, etc. used are those conventionally used in the art or can be easily obtained by a person of ordinary skill in the art according to the techniques conventionally used in the art.

[0014] Furthermore, the stirring speed in the first, third and fifth steps is 4000-6000 r / min.

[0015] Furthermore, the organic matter in the sixth step can form a certain adhesion with silicon oxide, and polyvinyl alcohol, sodium carboxymethyl cellulose, chitosan, etc. can be selected.

[0016] Furthermore, the filter membrane used in the vacuum-assisted filtration in the sixth step is a water filter membrane with a pore size of 0.1-0.8 μm.

[0017] Furthermore, during the calcination in the seventh step, the heating rate of the tubular furnace is 5°C / min, and the calcination temperature is preferably 700-1100°C.

[0018] Furthermore, the zirconium oxide-based composite film with a shell-like amorphous-crystalline dual-phase structure prepared by the method has a tensile strength of 1-25 MPa, a toughness of 0.005-0.3 MJ / m3, a hardness of 0.10-0.35 GPa, and a Young's modulus of 0.2-20 GPa.

[0019] Compared with the existing preparation strategy of zirconia-based composite materials with shell-like amorphous-crystalline dual-phase structure, the present invention has the following advantages:

[0020] 1. The raw materials used in the preparation process of the present invention are more widely used, non-toxic and harmless, and easy to obtain. The preparation method is green and simple, and the assembly strategy is universal.

[0021] 2. The amorphous-crystal dual-phase structure prepared by the present invention is orderly, which not only breaks through the problem of lack of methods for preparing dual-phase structures in the ceramic field, but also provides a new idea for constructing ordered amorphous-crystal dual-phase structures in other material fields.

[0022] 3. The present invention fully applies the bionic principle in the design of material structure. The prepared zirconium oxide-based composite film has a shell-like layered structure at the micrometer scale and a shell-like amorphous-crystalline dual-phase structure at the nanometer scale. Due to the unique shell-like structure of the composite film, it has both high strength and high toughness, breaking through the bottleneck that the strength and toughness of ceramic-based materials are difficult to improve simultaneously. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are optical photographs of the low amorphous content dual-phase composite ceramic thin film material obtained in Example 1 of the present invention and a cross-sectional scanning electron microscope photograph thereof.

[0024] Figure 2 This is a transmission electron microscope photograph of the low amorphous content dual-phase composite ceramic thin film material obtained in Example 1 of the present invention.

[0025] Figure 3 This is a stress-strain curve diagram of the low amorphous content dual-phase composite ceramic film material obtained in Example 1 of the present invention.

[0026] Figure 4 This is the force-intrusion depth curve of the low amorphous content dual-phase composite ceramic thin film material obtained in Example 1 of the present invention.

[0027] Figure 5 These are optical photographs of the medium-amorphous content dual-phase composite ceramic thin film material obtained in Example 2 of the present invention and scanning electron microscope photographs of its cross section.

[0028] Figure 6 This is a stress-strain curve diagram of the medium-amorphous content dual-phase composite ceramic film material obtained in Example 2 of the present invention.

[0029] Figure 7 This is the force-intrusion depth curve of the medium amorphous content dual-phase composite ceramic thin film material obtained in Example 2 of the present invention.

[0030] Figure 8 These are optical photographs of the high amorphous content dual-phase composite ceramic thin film material obtained in Example 3 of the present invention and a cross-sectional scanning electron microscope photograph thereof.

[0031] Fig. 9 This is a stress-strain curve diagram of the high amorphous content dual-phase composite ceramic film material obtained in Example 3 of the present invention.

[0032] Fig.10This is the force-intrusion depth curve of the high amorphous content dual-phase composite ceramic thin film material obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0033] The preparation method of the zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure is specifically described below in conjunction with the accompanying drawings and examples. However, it should be understood that these examples are only used to illustrate the present invention and do not limit the scope of protection of the present invention in any way.

[0034] Example 1

[0035] Preparation method of low amorphous content dual-phase composite ceramic film material

[0036] In the first step, 6.7 mL of concentrated hydrochloric acid and 18.4 g of tris(hydroxymethyl)aminomethane) were added to 1 L of ultrapure water to prepare a buffer solution with a pH value of 7.8. 108 mg of graphene oxide and 1.2 g of zirconium oxychloride octahydrate were added to the buffer solution in sequence, and the mixture was stirred at 55° C. for 5 h; wherein the concentration of the graphene oxide in the mixed solution was 0.09 mg / mL;

[0037] In the second step, the solution obtained in the first step is centrifuged at 6000 r / min for 5 minutes, the obtained precipitate is washed with ultrapure water for 1-5 times, and then the precipitate is dispersed in water, and a uniformly dispersed graphene oxide @ zirconium oxide nanosheet dispersion is obtained by ultrasonic treatment for 10-30 minutes, and the dispersion is fixed to volume for subsequent use;

[0038] The third step is to add the graphene oxide @ zirconium oxide nanosheet dispersion into 2L of anhydrous ethanol to obtain a uniformly dispersed brown-yellow suspension. Then, 84μL of tetraethyl silicate and 124mL of ammonia water are added in sequence, and the mixture is stirred at 25°C for 2h; wherein the concentration range of the graphene oxide @ zirconium oxide nanosheet in the mixed solution is 0.05mg / mL;

[0039] The fourth step is to centrifuge the reaction solution obtained in the third step at 6000 r / min for 5 minutes, wash the obtained precipitate with anhydrous ethanol and deionized water for 1-5 times respectively, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide @ silicon oxide nanosheet dispersion after 10-30 minutes of ultrasonic treatment, which is recorded as solution 1, and fix the volume for subsequent use;

[0040] Step 5: weigh 20-800 mg of organic matter using an analytical balance, add deionized water and stir to obtain a uniform solution, which is recorded as solution 2;

[0041] Step 6: Measure 6 mL of solution 2 in a 50 mL beaker, add 25 mg of graphene oxide @ zirconium oxide @ silicon oxide nanosheet solution 1, and then dilute to 40 mL with deionized water. Stir at room temperature for 36 h, and then assemble the nanosheets into a composite film by vacuum assisted filtration to obtain a black film sample.

[0042] In the seventh step, the film sample prepared in the sixth step is placed in a tube furnace and calcined at 1100°C for 2 hours to finally obtain a white composite film sample. The optical photo and cross-sectional scanning electron microscope photo are shown in FIG. Figure 1 As shown. From the scanning electron microscope image, it can be seen that the composite film presents a layered structure. The obtained sample was placed under a transmission electron microscope and it was found that the composite film has an ordered amorphous-crystalline dual-phase structure at the nanoscale ( Figure 2 ).

[0043] In the present invention, a universal mechanical testing machine tensile test is used to test the mechanical properties of the dual-phase structure composite material of Example 1, and a quasi-static nanoindentation is used to test the hardness and Young's modulus of the composite material. The test results show that the tensile strength of the composite film in Example 1 is 16.8MPa and the toughness is 0.02MJ / m 3 , ( Figure 3 ); hardness is 0.2GPa, Young's modulus is 3.2GPa ( Figure 4 ).

[0044] Example 2

[0045] Preparation method of medium amorphous content dual-phase composite ceramic film material

[0046] In the first step, 6.7 mL of concentrated hydrochloric acid and 18.4 g of tris(hydroxymethyl)aminomethane) were added to 1 L of ultrapure water to prepare a buffer solution with a pH value of 7.8. 108 mg of graphene oxide and 0.552 g of zirconium oxychloride octahydrate were added to the buffer solution in sequence, and the mixture was stirred at 55° C. for 5 h; wherein the concentration of the graphene oxide in the mixed solution was 0.09 mg / mL;

[0047] In the second step, the solution obtained in the first step is centrifuged at 6000 r / min for 5 minutes, the obtained precipitate is washed with ultrapure water for 1-5 times, and then the precipitate is dispersed in water, and a uniformly dispersed graphene oxide @ zirconium oxide nanosheet dispersion is obtained by ultrasonic treatment for 10-30 minutes, and the dispersion is fixed to volume for subsequent use;

[0048] The third step is to add the graphene oxide @ zirconium oxide nanosheet dispersion into 2L of anhydrous ethanol to obtain a uniformly dispersed brown-yellow suspension. Then, 84μL of tetraethyl silicate and 124mL of ammonia water are added in sequence, and the mixture is stirred at 25°C for 2h; wherein the concentration range of the graphene oxide @ zirconium oxide nanosheet in the mixed solution is 0.05mg / mL;

[0049] The fourth step is to centrifuge the reaction solution obtained in the third step at 6000 r / min for 5 minutes, wash the obtained precipitate with anhydrous ethanol and deionized water for 1-5 times respectively, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide @ silicon oxide nanosheet dispersion after 10-30 minutes of ultrasonic treatment, which is recorded as solution 1, and fix the volume for subsequent use;

[0050] Step 5: weigh 20-800 mg of organic matter using an analytical balance, add deionized water and stir to obtain a uniform solution, which is recorded as solution 2;

[0051] Step 6: Measure 6 mL of solution 2 in a 50 mL beaker, add 25 mg of graphene oxide @ zirconium oxide @ silicon oxide nanosheet solution 1, and then dilute to 40 mL with deionized water. Stir at room temperature for 36 h, and then assemble the nanosheets into a composite film by vacuum assisted filtration to obtain a black film sample.

[0052] In the seventh step, the film sample prepared in the sixth step is placed in a tube furnace and calcined at 1100°C for 2 hours to finally obtain a white composite film sample. The optical photo and cross-sectional scanning electron microscope photo are shown in FIG. Figure 5 From the scanning electron microscope image, it can be seen that the composite film presents a layered structure, and the layers are densely packed, and the number of large pores between the layers is reduced.

[0053] In the present invention, a universal mechanical testing machine tensile test is used to test the mechanical properties of the dual-phase structure composite material of Example 2, and a quasi-static nanoindentation is used to test the hardness and Young's modulus of the composite material. The test results show that the tensile strength of the composite film in Example 2 is 5.1MPa and the toughness is 0.006MJ / m 3 , ( Figure 6 ); hardness is 0.07GPa, Young's modulus is 1.7GPa ( Figure 7 ).

[0054] Example 3

[0055] Preparation method of high amorphous content dual-phase composite ceramic film material

[0056] In the first step, 6.7 mL of concentrated hydrochloric acid and 18.4 g of tris(hydroxymethyl)aminomethane) were added to 1 L of ultrapure water to prepare a buffer solution with a pH value of 7.8. 108 mg of graphene oxide and 0.096 g of zirconium oxychloride octahydrate were added to the buffer solution in sequence, and the mixture was stirred at 55° C. for 5 h; wherein the concentration of the graphene oxide in the mixed solution was 0.09 mg / mL;

[0057] In the second step, the solution obtained in the first step is centrifuged at 6000 r / min for 5 minutes, the obtained precipitate is washed with ultrapure water for 1-5 times, and then the precipitate is dispersed in water, and a uniformly dispersed graphene oxide @ zirconium oxide nanosheet dispersion is obtained by ultrasonic treatment for 10-30 minutes, and the dispersion is fixed to volume for subsequent use;

[0058] The third step is to add the graphene oxide @ zirconium oxide nanosheet dispersion into 2L of anhydrous ethanol to obtain a uniformly dispersed brown-yellow suspension. Then, 84μL of tetraethyl silicate and 124mL of ammonia water are added in sequence, and the mixture is stirred at 25°C for 2h; wherein the concentration range of the graphene oxide @ zirconium oxide nanosheet in the mixed solution is 0.05mg / mL;

[0059] The fourth step is to centrifuge the reaction solution obtained in the third step at 6000 r / min for 5 minutes, wash the obtained precipitate with anhydrous ethanol and deionized water for 1-5 times respectively, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide @ silicon oxide nanosheet dispersion after 10-30 minutes of ultrasonic treatment, which is recorded as solution 1, and fix the volume for subsequent use;

[0060] Step 5: weigh 20-800 mg of organic matter using an analytical balance, add deionized water and stir to obtain a uniform solution, which is recorded as solution 2;

[0061] Step 6: Measure 6 mL of solution 2 in a 50 mL beaker, add 25 mg of graphene oxide @ zirconium oxide @ silicon oxide nanosheet solution 1, and then dilute to 40 mL with deionized water. Stir at room temperature for 36 h, and then assemble the nanosheets into a composite film by vacuum assisted filtration to obtain a black film sample.

[0062] In the seventh step, the film sample prepared in the sixth step is placed in a tube furnace and calcined at 1100°C for 2 hours to finally obtain a white composite film sample. The optical photo and cross-sectional scanning electron microscope photo are shown in FIG. Figure 8 From the scanning electron microscope image, it can be seen that the composite film presents a layered structure, and the layers are stacked more closely, there are almost no large pores between the layers, and the number of small pores is also decreasing.

[0063] In the present invention, a universal mechanical testing machine tensile test is used to test the mechanical properties of the dual-phase structure composite material of Example 3, and a quasi-static nanoindentation is used to test the hardness and Young's modulus of the composite material. The test results show that the tensile strength of the composite film in Example 3 is 2.7MPa and the toughness is 0.003MJ / m 3 , ( Fig. 9 ); hardness is 0.03GPa, Young's modulus is 0.3GPa ( Fig.10 ).

Claims

1. A method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure, characterized in that The following steps are involved: The first step is to add 4-10 mL of concentrated hydrochloric acid and 10-20 g of tris(hydroxymethyl)aminomethane to 1 L of ultrapure water to prepare a buffer solution with a pH value of 5-8. Graphene oxide and zirconium oxychloride octahydrate are sequentially added to the buffer solution, and stirred at 40-90° C. for 1-7 hours; wherein the concentration range of the graphene oxide in the mixed solution is 0.05-0.17 mg / mL; the concentration range of the zirconium oxychloride octahydrate in the mixed solution is 0.08-1.00 mg / mL; The second step is to centrifuge the solution obtained in the first step at 4000-9000 r / min for 5 minutes, wash the obtained precipitate with ultrapure water for 1-5 times, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide nanosheet dispersion by ultrasonic treatment for 10-30 minutes, and then fix the volume for subsequent use; The third step is to add the graphene oxide @ zirconium oxide nanosheet dispersion into 2L of anhydrous ethanol to obtain a uniformly dispersed brown-yellow suspension. Then, tetraethyl silicate and ammonia water are added thereto in turn, and the reaction is stirred at 20-50°C for 2-9 hours; wherein the concentration range of the graphene oxide @ zirconium oxide nanosheet in the mixed solution is 0.01-0.1 mg / mL; the volume fraction of the tetraethyl silicate in the mixed solution is 0.01%-0.1%; the volume fraction of the ammonia water in the mixed solution is 7%-14%; The fourth step is to centrifuge the reaction solution obtained in the third step at 4000-9000 r / min for 5 minutes, wash the obtained precipitate with anhydrous ethanol and deionized water for 1-5 times respectively, disperse the precipitate in water, and obtain a uniformly dispersed graphene oxide @ zirconium oxide @ silicon oxide nanosheet dispersion after 10-30 minutes of ultrasonic treatment, which is recorded as solution 1, and fix the volume for subsequent use; Step 5: weigh 20-800 mg of organic matter using an analytical balance, add deionized water and stir to obtain a uniform solution, which is recorded as solution 2; Step 6: Measure 5-10 mL of solution 2 in a 50 mL beaker, add 10-50 mg of graphene oxide @ zirconium oxide @ silicon oxide nanosheet solution 1, 5, and then dilute to 40 mL with deionized water, stir at room temperature for 6-40 hours, and then assemble the nanosheets into a composite film by vacuum assisted filtration to finally obtain a black film sample; In the seventh step, the film sample obtained in the sixth step is placed in a tubular furnace and calcined at 500-1200° C. for 0.5-3 h to finally obtain a white composite film sample.

2. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: In the first step, graphene oxide is used as a template to uniformly grow zirconium oxide on its surface, wherein the thickness of the zirconium oxide nanolayer is controllable within the range of 1-10 nm.

3. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: In the third step, graphene oxide@zirconium oxide is used as a template to uniformly grow silicon oxide on its surface, wherein the thickness of the silicon oxide nanolayer can be controlled at 2-10 nm.

4. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: The organic matter in the fifth step has a certain adhesion on the surface of silicon oxide, and can be polyvinyl alcohol, sodium carboxymethyl cellulose, chitosan, etc., preferably polyvinyl alcohol.

5. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: The sample prepared in the sixth step is a black film with a certain degree of flexibility. It can be bent without breaking. The film thickness is controllable in the range of 2-60μm. The nanosheets inside the film are densely stacked to form an ordered layered structure similar to the nacre of shells.

6. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: The sample prepared in the seventh step has a certain light transmittance, the film thickness is controllable in the range of 1-40 μm, and the film has a layered structure.

7. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: The zirconium oxide-based film sample presents a layered structure at the micrometer scale and an ordered amorphous-crystalline dual-phase structure at the nanometer scale.

8. The method for preparing a zirconium oxide-based composite material having a shell-like amorphous-crystalline dual-phase structure according to claim 1, characterized in that: The tensile strength of the zirconium oxide-based film sample is 1-25MPa, and the toughness is 0.005-0.3MJ / m 3 , hardness is 0.10-0.35GPa, and Young's modulus is 0.2-20GPa.

Citation Information

Patent Citations

  • Fused quartz block for glass kiln hot repair and manufacturing method thereof

    CN101323531A

  • Preparation method of high-strength high-toughness zirconia nano-fiber

    CN109576820A

  • Preparation method of bionic high-strength high-flexibility nano composite fiber

    CN110396731A

  • Preparation method of lightweight high-strength zirconia-based heat insulation film

    CN119330705A